The influence of the nitrogen/nickel‐ratio on the cyclic behavior of austenitic high strength steels with twinning‐induced plasticity and transformation‐induced plasticity effects: Einfluss des Stickstoff‐/Nickel‐Verhältnisses auf das zyklische Verhalten austenitischer hochfester Stähle mit durch Zwillingsbildung und Umwandlung induzierter Plastizität. Issue 1 (30th January 2018) - Güler, S.; Schymura, M.; Fischer, A.; Droste, M.; Biermann, H.
Abstract: Austenitic high nitrogen (AHNS) and austenitic high interstitial steels (AHIS) are of interest for mechanical engineering applications because of their unique combination of mechanical (strength, ductility), chemical (corrosion resistance) and physical (non‐ferromagnetic) properties. But despite their high strength values e. g. after cold deformation up to 2 GPa in combination with an elongation to fracture of 30 %, which is based on twinning‐induced plasticity (TWIP) mechanisms and transformation‐induced plasticity (TRIP) mechanisms, the fatigue limit remains relatively small. While for chromium‐nickel steels the fatigue limit rises with about 0.5‐times the elastic limit it does not at all for austenitic high‐nitrogen steels or only to a much smaller extent for nickel‐free austenitic high‐interstitial steels. The reasons are still not fully understood but this behavior can roughly be related to the tendency for planar or wavy slip. Now the latter is hindered by nitrogen and promoted by nickel. This contribution shows the fatigue behavior of chromium‐manganese‐carbon‐nitrogen (CrMnCn) steels with carbon+nitrogen‐contents up to 1.07 wt.%. Beside the governing influence of these interstitials on fatigue this study displays, how the nitrogen/nickel‐ratio might be another important parameter for the fatigue behavior of such steels.